Mergers & Acquisition in the Luxury Goods Industry - An Assessment of drivers &strategies. - Jain, Kanishka (2011)
The luxury goods industry has undergone a significant change of paradigms during the three elapsed decades. Luxury industry is a collective term for companies selling – besides high-quality products – principally status, emotional benefit, prestige and exclusivity as well as the dream of separation from the ordinary may be traditional since the mid 1980s. Since that time, this conceptual term has shaped both the self-conception of the industry and its perception by customers. Moreover, the mid 80s had been a phase when several luxury companies were formed and repositioned. In the early 1990s, market actors became aware of the tougher competitive situation within this industry segment. This awareness marked the beginning of consolidation activities increasingly intensifying until the year 2000 when the number of transactions climaxed. (Berry 1994)